The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11864-021-00910-8
|View full text |Cite
|
Sign up to set email alerts
|

Treating Chronic Pain with Buprenorphine—The Practical Guide

Abstract: Buprenorphine has unique and favorable pharmacological properties that make it useful in a variety of clinical scenarios. It has been recommended to consider buprenorphine first-line opioid for chronic pain, especially in the elderly as it may be associated with less cognitive impairment, falls, sexual dysfunction, and sarcopenia when compared with schedule II opioids. It may be useful in patients with comorbid substance use disorder or non-medical opioid use, as there is less risk of misuse, euphoria and it m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
(56 reference statements)
0
11
0
2
Order By: Relevance
“…A study involving chronic cancer pain and non-cancer pain found that the sublingual buprenorphine to oral morphine ratio of 42 was accurate for 70% of patients 5. The equivalents published by Case et al are a reasonable table to use when rotating 6…”
Section: Initiating Opioid Therapymentioning
confidence: 99%
“…A study involving chronic cancer pain and non-cancer pain found that the sublingual buprenorphine to oral morphine ratio of 42 was accurate for 70% of patients 5. The equivalents published by Case et al are a reasonable table to use when rotating 6…”
Section: Initiating Opioid Therapymentioning
confidence: 99%
“…Asimismo, en el caso de cáncer terminal es el único tratamiento que es factible ofrecer porque mejora el dolor, la astenia, la anorexia, la caquexia y los trastor-nos psicológicos con el objetivo de mejorar la calidad de vida. 58 Se ha demostrado que en los pacientes con diferentes tipos de cáncer gastrointestinal que reciben cuidados paliativos, el desgaste muscular se comporta como un factor pronóstico negativo, con un predominio en el sexo masculino. 59 El dolor es uno de los síntomas más difíciles de tratar durante la etapa paliativa del cáncer.…”
Section: Efectos Del Tratamiento Paliativo Y Otros Tratamientosunclassified
“…Lo anterior contribuye a las dificultades para el control del dolor especialmente en pacientes con caquexia. 58,59 Recientemente se ha empleado también el uso de cannabinoides (CBD) en tratamiento paliativo del cáncer. 60 Se han realizado estudios en investigación en ratones con respecto a la expresión diferencial de los receptores de cannabinoides CB1 y CB2 y ha destacado que la expresión de CB2 mejora con el ejercicio al promover la capacidad regenerativa del músculo mediada por Pax7 y MyoD, lo cual alienta a explorar el CBD en el tratamiento de la sarcopenia en este grupo de pacientes.…”
Section: Efectos Del Tratamiento Paliativo Y Otros Tratamientosunclassified
“… 7 Compared to full opioid agonists, the action of buprenorphine at MORs produces a high-potency analgesic effect with fewer adverse effects, such as physical dependence, respiratory depression, and constipation. 7 , 9 However, due to buprenorphine’s high MOR affinity and slow dissociation, the competitive binding of MORs can precipitate opioid withdrawal in the presence of full opioid agonists. 7 , 10 As such, current bup/nal product monographs require patients to discontinue their existing opioid therapy and experience mild-to-moderate withdrawal symptoms prior to bup/nal initiation to avoid abrupt displacement at MORs.…”
Section: Introductionmentioning
confidence: 99%